2016
DOI: 10.1089/jop.2015.0080
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pupil Size Following Panretinal and Focal/Grid Retinal Photocoagulation: Automatic Infrared Pupillometry Study

Abstract: We have demonstrated through automated infrared pupillary measurements that panretinal laser photocoagulation may significantly influence pupil size and focal/grid laser photocoagulation may not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Спустя 1 месяц в группе с панретинальной фотокоагуляцией наблюдалось значительное увеличение размера зрачка, а в группе с фокусной фотокоагуляцией значительного изменения не зафиксировано. С помощью автоматизированной инфракрасной пупиллометрии удалось продемонстрировать, что панретинальная фотокоагуляция сетчатки может значительно влиять на изменение размера зрачка, в то время как фокусная фотокоагуляция сетчатки особого влияния не оказывает [9]. K. Tekin и соавт.…”
Section: рис 2 пупиллометр гаабаunclassified
“…Спустя 1 месяц в группе с панретинальной фотокоагуляцией наблюдалось значительное увеличение размера зрачка, а в группе с фокусной фотокоагуляцией значительного изменения не зафиксировано. С помощью автоматизированной инфракрасной пупиллометрии удалось продемонстрировать, что панретинальная фотокоагуляция сетчатки может значительно влиять на изменение размера зрачка, в то время как фокусная фотокоагуляция сетчатки особого влияния не оказывает [9]. K. Tekin и соавт.…”
Section: рис 2 пупиллометр гаабаunclassified
“…They concluded that conventional laser treatment caused more intense laser burns compared to the PASCAL laser and caused more damage to the ciliary nerves. In another study by Yilmaz et al, 21 in which patients with diabetic retinopathy who underwent panretinal photocoagulation and focal laser photocoagulation were assessed with automated infrared pupillometry; it was reported that the panretinal photocoagulation group had significantly increased basal measurements of pupil diameters in all lighting conditions, while there was no significant change in the focal laser photocoagulation group. Although there are studies in the literature which examine the effects of laser photocoagulation on pupil diameter, there is lack of evidence on dynamic pupil responses in eyes with retinal vein occlusion that underwent retinal laser photocoagulation.…”
Section: Presented Four Cases In Which Thementioning
confidence: 99%